Advances in Nature and Biologically Inspired Computing Proceedings of the 7th World Congress on Nature and Biologically Inspired Computing (NaBIC2015) in Pietermaritzburg, South Africa, held December 01-03, 2015 - Pillay, Nelishia; Engelbrecht, Andries P.; Abraham, Ajith; du Plessis, Mathys C.; Snášel, Václav; Muda, Azah Kamilah (Advances in Intelligent Systems and Computing, 2016)
World Congress on Nature and Biologically Inspired Computing (NaBIC) is organized to discuss the state-of-the-art as well as to address various issues with respect to Nurturing Intelligent Computing Towards Advancement of Machine Intelligence. This Volume contains the papers presented in the Seventh World Congress (NaBIC'15) held in Pietermaritzburg, South Africa during December 01-03, 2015. The 39 papers presented in this Volume were carefully reviewed and selected. The Volume would be a valuable reference to researchers, students and practitioners in the computational intelligence field.